The Sendai Framework and Satellite Security - Jessie Hamill-Stewart (International Journal of Disaster Risk Science)
Abstract The Sendai Framework for Disaster Risk Reduction 2015–2030 (SFDRR) aims to play a fundamental role in increasing global resilience. The focus of this research is to consider analysis of risks and recovery related to satellite disruption within the context of the SFDRR. Analysis of satellite disruption has often been more technical and less focused on supporting recovery. This research considers the framework’s relevance for preventing disruption to satellite systems and global recovery measures for related disasters that emerge due to dependence on satellites. First, the use of space terminology within the framework is considered. Next, principles within the SFDRR that are relevant to satellite system disruption are highlighted, and this is followed by presentation of key gaps relevant to this disruption, before potential improvements to expand the framework are proposed. This article outlines how concepts within the SFDRR could help to improve recovery from a disaster that occurs due to worst-case-scenario type satellite disruption. In this case, critical satellites are disrupted, preventing access to fundamental services such as navigation and timing. The aims of this research are to consider how the SFDRR can be expanded to consider disruption to critical satellite systems, by identifying aspects of the framework that are applicable to this type of disaster. Another outcome is to contribute to wider disaster recovery literature by encouraging consideration of disasters involving disruption to digital services.